Lingvocultural Specifics of the Communicative Behaviour in Arabic English-language Business Discourse - L. A. Kochetova; Yassien Sh. S. Al-Bayati (Дискурс, 2021)
Introduction. The paper studies specifics of the communicative behavior of native speakers of English and Arab speakers of English as a second language in business situations. The novelty of the study is implied by the fact that it establishes ethnocultural features of comissive speech acts in value-marked situations in the English-language business discourse. The relevance of the study is conditioned by the interest in speech acts functioning in lingvocultural perspective, which studies patterns of communicative behavior in cross-cultural situations and issues of verbal representation of speech acts in the speech of native and non-native speakers of English as they are employed in various genres and types of discourse.Methodology and sources. The study employs methods of corpus linguistics and discourse analysis interpretive method. The study is drawn on a corpus compiled of business letters written by employees of United Arab Emirates companies who speak English as a second language (LBLC). The corpus LBLC comprises 160 letters, 33 907 words. To identify cultural differences, Business Letter Corpus of 1 million words that contains letters written by British and American writers was chosen.Results and discussion. The results of cross-cultural comparison of commissive speech acts representation in value marked situations in the Learner Business Letter Corpus (LBLC) and Business Letter Corpus are presented. It has been concluded that both corpora under study display similarity as for functions of comissive speech acts in value-marked communicative situations whereas differences are revealed in the variation of lexical and grammatical choices that represent these speech acts and their pragmatics. In the BLC the situations when commissive speech acts correlate with apology the addresser commits themselves to obligation not to perform actions that are undesirable for the addressee or prevent the circumstances that might have negative consequences for the addressee. In the LBLC, following the communicative act of apology the addresser emphasizes the causes that have resulted in his failure to complete his obligations and promises to eliminate these causes. The texts in BLC employ explicit speech acts of guarantee that represent an obligation on condition that the addressee completes a certain action and emphasize the sincerity of the addresser. The texts in LBLC do not contain any instances of explicit speech acts of guarantee and the utterance is interpreted as a guarantee on the basis of declarations expressed in the letter.Conclusion. It is concluded that in cross-cultural value-marked situations speech acts implementation follows algorithms that are relevant in a given culture and display cultural specificity that can be studies by linguistic methods.